Is successful integration of land-use and transport planning centred around a catalytic city-wide public transport network improvement project? - Boshielo, Shela Paulina Polly (Department of Civil Engineering, 2019)
This case study showed that land-use and transport planning in South Africa are not successfully integrated. In addition, the institutional arrangements governing land-use and transport planning are not properly aligned and operate in silos. This study investigated various mechanisms that can be used to successfully integrate land-use and transport planning. The main purpose of this study was to find the common key features of successful integrated land-use and transport planning. The study was based on a case study method. The data was collected from secondary sources in three widely-acclaimed international cities that have implemented land-use and transport planning. The major finding of the study was that successful integration of land-use and transport planning are centred on a catalytic city-wide public transport network improvement project. All three international case studies (Curitiba, Portland and Copenhagen) that were studied, have successfully integrated its land-use and transport planning, and had a catalytic public transport network project at its core. The study concluded that, to be successful, the integration of land-use and transport planning need to be centred on a catalytic city-wide public transport network improvement project.